Profilin-1 overexpression restores adherence junctions in MDA-MB-231 breast cancer cells in R-cadherin dependent manner - Zou, Li (2009)
Profilin-1 (Pfn1), a ubiquitously expressed actin-binding protein, is downregulated in several different types of adenocarcinoma and elicits tumor-suppressive effect on breast cancer cell lines. MDA-MB-231 (MDA-231), a breast cancer cell line that displays all the characteristics of post-epithelial-to-mesenchymal transition and does not form cell-cell adhesion, can be reverted to an epithelioid phenotype by Pfn1 overexpression. This morphological transition is caused by restoration of adherence junctions (AJ) requiring Pfn1’s interaction with actin. Pfn1 overexpression increases the expression level of R-cadherin (a type of cadherin that is endogenously expressed in the parental cell line) and restores AJ in MDA-231 cells in R-cadherin dependent manner. These findings highlight important role of Pfn1 in the regulation of epithelial cell-cell adhesion.